Pei-cqds composites, gels and methods of making the same

CN119613954BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311174750.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2026-10-16
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

现有技术制备的高分子量的聚乙烯亚胺,主要是国外的巴斯夫和日本触媒公司,国内仅有少数企业进行PEI的生产,原因主要是原料乙烯亚胺生产企业很少,以及乙烯亚胺聚合制备PEI技术不过关,而低分子量的聚乙烯亚胺(尤其是分子量低于2000g/mol的PEI)却难以应用于堵水剂中

Benefits of technology

[0016] In this invention, graphite rods are used as anodes and cathodes and carbon source, and water is used as electrolyte solution to prepare carbon quantum dots. The experimental process is simple, green and environmentally friendly, and small-sized CQDs are obtained. Moreover, under preferred conditions, CQDs that are more suitable for solving the technical problems of this invention can be prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613954B_ABST
    Figure CN119613954B_ABST
Patent Text Reader

Abstract

The present application relates to the field of gel, disclose PEI-CQDs composite material, gel and their preparation method, the preparation method of the PEI-CQDs composite material includes: (1) graphite is electrolyzed in water, obtain carbon quantum dots;(2) carbon quantum dots and polyethylene imine are reacted in the presence of optional adjuvant, obtain PEI-CQDs composite material.The PEI-CQDs composite material can be applied to the preparation process of gel, so that low molecular weight PEI can also be used for preparing gel, and the gel time can be shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gels, specifically to a method for preparing a PEI-CQDs composite material, the PEI-CQDs composite material prepared by the method, the application of the PEI-CQDs composite material in gel preparation, a method for preparing a gel, and a gel. Background Technology

[0002] Carbon quantum dots (CQDs), as a novel type of carbon nanomaterial, possess advantages such as small particle size, large specific surface area, numerous active sites on the surface, good water solubility, and ease of functionalization. The abundant oxygen-containing functional groups on the surface, such as carboxyl, hydroxyl, and epoxy groups, cause them to become negatively charged upon hydrolysis in water.

[0003] Polyethyleneimine (PEI) is a water-soluble polymer. As a typical gel-type water-blocking agent, PEI gel has advantages such as low surface viscosity, easy preferential penetration into high-permeability layers, adjustable freezing time and gel strength, and low toxicity. Currently, high-molecular-weight polyethyleneimine is mainly produced by BASF and Nippon Shokubai Corporation abroad, with only a few domestic companies producing PEI. This is primarily due to the limited number of raw material ethyleneimine producers and the inadequate technology for polymerizing ethyleneimine to prepare PEI. Furthermore, low-molecular-weight polyethyleneimine (especially PEI with a molecular weight below 2000 g / mol) is difficult to apply in water-blocking agents. Summary of the Invention

[0004] The purpose of this invention is to overcome the problem that low molecular weight PEI is difficult to apply to the production of water-blocking agents, and to provide a PEI-CQDs composite material and its preparation method. The PEI-CQDs composite material can be applied to the gel preparation process, so that low molecular weight PEI can also be used to prepare gels, and the gelation time can be shortened.

[0005] To achieve the above objectives, the first aspect of the present invention provides a method for preparing PEI-CQDs composite materials, the method comprising:

[0006] (1) Electrolyze graphite in water to obtain carbon quantum dots;

[0007] (2) Carbon quantum dots and polyethyleneimine are reacted in the presence of optional additives to obtain PEI-CQDs composite material.

[0008] Preferably, in step (1), the preparation method of the carbon quantum dots includes: using a graphite rod as the anode and cathode, electrolyzing water using a DC power supply to obtain an electrolyte, purifying the electrolyte, and obtaining carbon quantum dots.

[0009] Preferably, the voltage is 5-50V, more preferably 10-40V.

[0010] The PEI-CQDs composite material prepared by the method provided in the second aspect of the present invention.

[0011] A third aspect of the present invention provides a PEI-CQDs composite material, wherein the PEI-CQDs composite material comprises polyethyleneimine covalently modified with carbon quantum dots;

[0012] Among the oxygen-containing functional groups on the surface of carbon quantum dots, the molar ratio of hydroxyl to carbonyl groups is less than 1.

[0013] The fourth aspect of the present invention provides the use of the PEI-CQDs composite material as described above in the preparation of gels; preferably in the preparation of polyacrylamide gels.

[0014] The fifth aspect of the present invention provides a method for preparing a gel, the method comprising: contacting and reacting the PEI-CQDs composite material as described above with polyacrylamide in the presence of water to obtain a gel.

[0015] The sixth aspect of the present invention provides a gel prepared by the method described above.

[0016] In this invention, graphite rods are used as anodes and cathodes and carbon source, and water is used as electrolyte solution to prepare carbon quantum dots. The experimental process is simple, green and environmentally friendly, and small-sized CQDs are obtained. Moreover, under preferred conditions, CQDs that are more suitable for solving the technical problems of this invention can be prepared.

[0017] This invention grafts PEI with CQDs. Grafting not only alters the physical and chemical properties of PEI to a certain extent and improves its functionality, but also effectively increases the molecular weight and branching degree of PEI. This allows low molecular weight PEI to be used to prepare gels, shortens the gelation time, and improves the performance of the prepared gel water-blocking agent.

[0018] The quantum dot preparation, composite material preparation, and gelation reaction of this invention all utilize an aqueous system, and the entire preparation process does not use organic solvents. The prepared carbon quantum dots can be used directly in solution without separation. Moreover, the preparation method is simple, the preparation process conditions are easy to control, high temperatures are not required, raw materials are readily available, the entire preparation system is environmentally friendly and safe, batches are stable, and the price is low, showing good application prospects. Attached Figure Description

[0019] Figure 1 These are transmission electron microscope images of the CQDs prepared in Example 1 of this invention;

[0020] Figure 2 XPS full spectrum image of CQDs prepared in Example 1 of this invention;

[0021] Figure 3 This is the XPS spectrum of C1s of the CQDs prepared in Preparation Example 1 of this invention;

[0022] Figure 4 The PEI used in Embodiment 1 of this invention 600 CQDs prepared in Example 1 and PEI prepared in Example 1 600 -Infrared spectra of CQDs;

[0023] Figure 5 The PEI used in Embodiment 1 of this invention 600 CQDs prepared in Example 1 and PEI prepared in Example 1 600 -CQDs, PEI 1800 -CQDs and PEI 10000 -Infrared spectra of CQDs;

[0024] Figure 6 For PEI 1800 GPC spectrum;

[0025] Figure 7 For PEI 1800 GPC spectra of -CQDs;

[0026] Figure 8 PAM / PEI prepared for PEI of different molecular weights (from left to right: PAM / PEI) 3000 PAM / PEI 10000 PAM / PEI 25000 Gel map;

[0027] Figure 9 PAM / CQDs / PEI prepared for PEI of different molecular weights (from left to right: PAM / CQDs / PEI) 3000 PAM / CQDs / PEI 10000 PAM / CQDs / PEI 25000 Gel map;

[0028] Figure 10 Gel images prepared with different amounts of CQDs, where the left image shows 0.05g PAM and 2mL PEI. 25000 -CQDs, PEI:CQDs=10:1 (mass ratio), the right figure shows 0.05g PAM, 2mL PEI 25000 -CQDs, where PEI:CQDs = 5:1 (mass ratio). Detailed Implementation

[0029] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0030] The first aspect of this invention provides a method for preparing PEI-CQDs composite materials, the method comprising:

[0031] (1) Electrolyze graphite in water to obtain carbon quantum dots;

[0032] (2) Carbon quantum dots and polyethyleneimine are reacted in the presence of optional additives to obtain PEI-CQDs composite material.

[0033] Preferably, in step (1), the preparation method of the carbon quantum dots includes: using a graphite rod as the anode and cathode, electrolyzing water using a DC power supply to obtain an electrolyte, purifying the electrolyte, and obtaining carbon quantum dots.

[0034] It should be understood that the graphite rod can be cleaned before electrolysis, for example, by using deionized water and anhydrous ethanol, with ultrasonic treatment accompanying the cleaning process. The size of the graphite rod can be a conventional size in the art, and it should be placed in a conventional manner for electrolysis. Preferably, the diameters of the cathode graphite rod and the anode graphite rod are each independently 0.3-1 cm.

[0035] Preferably, the distance between the cathode graphite rod and the anode graphite rod is 3-15 cm, more preferably 5-10 cm.

[0036] Generally, during electrolysis, the anode graphite rod first produces bubbles, and the solution gradually changes from colorless to yellow. As the electrolysis process continues, the anode graphite rod corrodes, gradually turning the solution a deep yellow until it becomes completely black. In this invention, there is no particular limitation on the electrolysis time; it can be selected as needed, as long as carbon quantum dots can be obtained. For example, the time can be 96-360 hours.

[0037] Preferably, the voltage is 5-50V, more preferably 10-40V.

[0038] The water can be deionized water or ultrapure water, etc., and preferably, the conductivity of the water is less than 10 μS / cm.

[0039] The inventors of this invention have discovered that, under the preferred voltage conditions, when electrolysis is performed using water as the electrolyte, the proportion of carbonyl groups (carbon-oxygen double bonds) in the oxygen-containing functional groups on the surface of carbon quantum dots can be further increased, thereby further reducing the molar ratio of hydroxyl groups (carbon-oxygen single bonds) to carbon quantum dots.

[0040] The purification method can be a conventional method in the art, such as purification through solid-liquid separation and dialysis. Specifically, large particles can be removed by filtration, followed by further purification by dialysis (dialysis for 2-4 days, changing deionized water every 2-6 hours). The purified solution can be used directly for the preparation of composite materials, or it can be used after drying. The drying method can be a conventional method in the art, such as freeze-drying.

[0041] When the CQDs exist in powder form, they can be dispersed in deionized water before mixing with PEI to obtain a uniform and stable dispersed solution. A description of the properties of the CQDs is provided in Section III and will not be repeated here.

[0042] Preferably, in step (2), the ratio of polyethyleneimine to carbon quantum dots by weight is 0.1-20:1, for example, it can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1 and any range between any two values, more preferably 1-15:1.

[0043] Preferably, the molecular weight (Mw) of polyethyleneimine is 500-50000 g / mol, for example, it can be 500, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000, 3000, 4000, 50000 g / mol and any range between any two values, more preferably 600-20000 g / mol.

[0044] In one embodiment of the present invention, in step (2), the additive comprises a crosslinking agent and / or an amino protectant.

[0045] Preferably, the crosslinking agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl).

[0046] Preferably, the amino protecting agent is N-hydroxysuccinimide (NHS).

[0047] Preferably, the solvent is water. The solvent may include solvents in PEI solutions and CQDs solutions.

[0048] Preferably, the ratio of carbon quantum dots, crosslinking agent and amino protecting agent by weight is 1:0.2-10 (e.g., 0.2, 0.5, 1, 2, 4, 6, 8, 10 and any range between any two values) : 0.1-5 (e.g., 0.1, 0.5, 1, 2, 3, 4, 5 and any range between any two values), more preferably 1:0.5-5:0.2-2.

[0049] When adding additives, the preferred order of addition is to add the crosslinking agent and amino protecting agent to the CQDs solution, followed by the PEI solution. The PEI solution can be added dropwise.

[0050] Preferably, the solvent is water. The solvent may include the solvent in the PEI solution and the CQDs solution, as well as any additional solvents added. The solvent may be water, such as deionized water or ultrapure water, and preferably, the conductivity of the solvent is less than 10 μS / cm.

[0051] There is no particular limitation on the amount of solvent, as long as the reaction can proceed normally. Preferably, the ratio of carbon quantum dots to solvent by weight is 1:10-1000, and more preferably 1:50-500.

[0052] The reaction may be accompanied by auxiliary measures such as stirring and / or ultrasound. There are no special restrictions on the reaction temperature, which can be carried out at room temperature. The reaction time can be based on the completeness of the reaction, such as 12-36 hours.

[0053] After the reaction is complete, the reacted material can be purified. For example, the lower precipitate can be removed by filtration, and then the upper solution can be dialyzed to remove the uncrosslinked PEI. The dialyzed product is then dried (e.g., freeze-dried) to obtain the composite material.

[0054] In this invention, the specific purification conditions can be those conventional purification methods used in the field, and will not be elaborated here.

[0055] The second aspect of the present invention provides a PEI-CQDs composite material prepared by the method described above.

[0056] For information on the properties of the composite material, please refer to the third aspect, which will not be repeated here.

[0057] A third aspect of the present invention provides a PEI-CQDs composite material, wherein the PEI-CQDs composite material comprises polyethyleneimine covalently modified with carbon quantum dots;

[0058] Among the oxygen-containing functional groups on the surface of carbon quantum dots, the molar ratio of hydroxyl to carbonyl groups is less than 1, for example, it can be 0.1, 0.2, 0.4, 0.6, 0.8, 0.9, 0.95 and any range between any two values, preferably 0.2-0.6.

[0059] Among them, the molar ratio of hydroxyl to carbonyl groups in the oxygen-containing functional groups on the surface of carbon quantum dots is determined by XPS of carbon quantum dots.

[0060] Preferably, the infrared spectrum of the PEI-CQDs composite material includes 1632-1638 cm⁻¹. -1 (For example, it could be 1632, 1634, 1636, 1638cm) -1 The stretching vibration of C=C at any range between any two values.

[0061] Preferably, the average particle size of the CQDs is 2-8 nm (for example, it can be 2, 4, 6, 8 nm or any range between any two values).

[0062] Preferably, carbon quantum dots are obtained by electrolysis of graphite. For details of the electrolysis method, please refer to the first aspect.

[0063] Preferably, by weight, the ratio of the polyethyleneimine-derived portion to the carbon quantum dot portion in the PEI-CQDs composite material is 0.1-20:1, for example, it can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1, or any range between any two values, more preferably 1-15:1.

[0064] Preferably, the molecular weight (Mw) of the PEI-CQDs composite material is 2000-100000 g / mol, for example, it can be 2000, 5000, 10000, 20000, 40000, 60000, 80000, 100000 g / mol and any range between any two values.

[0065] Preferably, the molecular weight (Mw) of the polyethyleneimine (PEI) moiety is 500-50000 g / mol, for example, it can be 500, 1000, 5000, 10000, 20000, 30000, 40000, 50000 g / mol and any range between any two values; more preferably, it is 600-20000 g / mol.

[0066] The fourth aspect of the present invention provides the use of the PEI-CQDs composite material as described above in the preparation of gels; preferably in the preparation of polyacrylamide gels.

[0067] The fifth aspect of the present invention provides a method for preparing a gel, the method comprising: contacting and reacting polyacrylamide with water in the presence of the PEI-CQDs composite material as described above to obtain a polyacrylamide gel.

[0068] Preferably, the reaction conditions include a temperature of 60-120°C, more preferably 80-110°C.

[0069] There is no particular limitation on the reaction time, as long as there is enough time to form a gel, such as more than 2 hours, preferably 10-50 hours.

[0070] Preferably, the ratio of polyacrylamide to PEI-CQDs by weight is 100:2-20.

[0071] Preferably, the mass ratio of polyacrylamide to water is 0.1-15:100 by weight.

[0072] The sixth aspect of the present invention provides a gel prepared by the method described above.

[0073] The present invention will be described in detail below through embodiments.

[0074] Unless otherwise specified, all reagents and materials used were obtained commercially.

[0075] In the following examples, PEI of different molecular weights were all purchased from Sinopharm Reagent Company, and their molecular weights are indicated by subscripts, such as PEI. 1800 Its molecular weight is 1800 g / mol.

[0076] The molar ratio of hydroxyl to carbonyl groups in the oxygen-containing functional groups on the surface of carbon quantum dots is determined by XPS.

[0077] The infrared spectrum of the PEI-CQDs composite material was determined by FT-IR.

[0078] Preparation Example 1

[0079] First, place a 15cm long, 0.6cm diameter graphite rod into a 500mL beaker, add deionized water and anhydrous ethanol sequentially, and ultrasonically clean each for 30 minutes. Then, dry the rod. Using tweezers, handle the cleaned graphite rod and insert one rod as the cathode into 1000mL of deionized water, placing it parallel to the anode rod, with a 5.5cm gap between them. Electrolyze at 15V DC for 240 hours until the solution turns completely black. After electrolysis, filter to remove large particles, concentrate by rotary evaporation, and dialyze for 3 days, changing the deionized water every 8 hours. Freeze-dry the dialyzed solution for 48 hours until completely dry into powder to obtain CQDs, which are then stored for later use.

[0080] Transmission electron microscopy images of the CQDs are as follows: Figure 1 As shown, it can be seen that the whole is composed of spherical nanoparticles.

[0081] XPS full spectrum images of the CQDs are as follows: Figure 2 As shown, it can be seen that it contains only carbon and oxygen. Figure 3 XPS spectra of the C1s of the CQDs are shown, with a molar ratio of hydroxyl to carbonyl groups of 0.5 in the oxygen-containing functional groups. The average particle size of the CQDs was determined to be 3-5 nm.

[0082] Preparation Example 2

[0083] The procedure was performed according to the method described in Preparation Example 1, except that the voltage was different, specifically 30V.

[0084] The CQDs obtained were basically the same in shape as those obtained in Preparation Example 1, with a particle size of 4-7 nm and a molar ratio of hydroxyl to carbonyl groups of 0.3 in the oxygen-containing groups.

[0085] Preparation Example 3

[0086] The procedure was carried out according to the method described in Preparation Example 1, except that the solvent was different, specifically ethanol.

[0087] The CQDs prepared were basically the same in shape as those prepared in Preparation Example 1, with a particle size of 2-5 nm and a molar ratio of hydroxyl to carbonyl groups of 0.8 in the oxygen-containing groups.

[0088] During the experiment, the inventors discovered that when the molar ratio of hydroxyl to carbonyl groups in the CQDs prepared in Examples 1-3 was lower, it would be beneficial to promote the grafting of PEI to CQDs, thereby further improving the performance of PEI-CQDs in preparing gels.

[0089] Example 1

[0090] This embodiment is used to illustrate PEI. 600 Preparation method of -CQDs composite materials.

[0091] First, using an electronic balance, 0.2 g of the CQDs powder prepared in Example 1 was added to a 50 mL beaker containing 40 mL of deionized water. The mixture was ultrasonically vibrated to completely dissolve and disperse the CQDs powder in the deionized water, obtaining a uniform and stable dispersion solution. Then, using an electronic balance, 400 mg of EDC·HCl and 240 mg of NHS were added, followed by 2 g of PEI. 600In this experiment, PEI was added dropwise to the CQDs aqueous solution in at least three separate additions. A magnetic stir bar was added to the beaker, and the mixture was stirred at room temperature for 24 hours to ensure complete reaction. The mixture was then washed 3-4 times with deionized water, centrifuged to remove the lower precipitate, and the upper black solution was collected. Dialysis was performed to remove uncrosslinked PEI, followed by freeze-drying for 24 hours to obtain PEI-CQDs (denoted as PEI). 600 -CQDs) powder, store for later use.

[0092] For PEI 600 Infrared testing was performed on CQDs and PEI-CQDs, and the test spectra are shown below. Figure 4 As shown. From Figure 4 It can be observed that the spectra of CQDs contain a broad absorption peak, followed by several overlapping peaks. Most of these bands are due to characteristic vibrations of chromophores from different functional groups within the CQDs' internal structure. Most bands in the unmodified CQDs' spectra are associated with characteristic bonds in CH and C@C organic compounds, some of which originate from dehydration steps. The peak is at 3419 cm⁻¹. -1 Corresponding to the stretching vibration of the OH bond; the second band is in the 1500-2000 cm⁻¹ range. -1 Between, caused by the stretching of C=O in CQDs, containing 1624cm -1 and 1700cm -1 The peak value was at 1444cm; while at 1444cm -1 This is due to the bond in the aliphatic CH3 group at point C, 1239cm -1 The peak at 1668 cm⁻¹ represents the bending vibration of saturated CH₄. As can be seen from the figure, the spectra of PEI-CQDs exhibit all the characteristic absorption features of PEI, with a peak at 1668 cm⁻¹. -1 This is attributed to C-NH stretching. This result confirms that PEI successfully covalently modifies CQDs. PEI composite material 600 -CQDs compared to PEI 600 1635cm added -1 The stretching vibration of C=C.

[0093] Example 2

[0094] This embodiment illustrates the preparation method of PEI-CQDs composite materials.

[0095] The procedure was performed according to the method described in Example 1, except that equal masses of PEI with different molecular weights were used instead of PEI. 600PEI-CQDs powder was obtained and stored for later use. The molecular weights of PEI were 1800 g / mol, 3000 g / mol, 10000 g / mol, and 25000 g / mol, respectively. The obtained PEI-CQDs were denoted as PEI-CQDs. 1800 -CQDs, PEI 3000 -CQDs, PEI 10000 -CQDs and PEI 25000 -CQDs, where PEI 1800 -CQDs and PEI 10000 -Infrared spectra of CQDs as follows Figure 5 As shown, C=C stretching vibrations also exist, confirming that PEI has successfully performed covalent modification on CQDs.

[0096] The grafting effects of PEI with CQDs of different molecular weights were compared, and the results are shown in Table 1.

[0097] Table 1

[0098] <![CDATA[PEI 600 -CQDs]]> Centrifugation basically does not separate the layers. A viscous colloid, somewhat similar to the original PEI. <![CDATA[PEI 1800 -CQDs]]> Centrifugation only resulted in a small portion of the layers separating. gelatinous black solid <![CDATA[PEI 3500 -CQDs]]> Centrifugation only resulted in a small portion of the layers separating. gelatinous black solid <![CDATA[PEI 10000- CQDs]]> Centrifugation essentially resulted in complete stratification. gelatinous black solid <![CDATA[PEI 25000- CQDs]]> Centrifugation essentially resulted in complete stratification. gelatinous black solid

[0099] Figure 6 and Figure 7 The distribution shows PEI 1800 and PEI 1800 The GPC spectra of -CQDs show that the sharper peaks in both graphs are solvent peaks, with deionized water as the solvent and polyethylene glycol as the standard. Because the test is affected by factors such as the structure of the substance, molecular morphology, the selected mobile phase, and the standard, the measured molecular weight may have some deviation. However, under the same conditions, the modified PEI-CQDs showed an additional peak at 2895, indicating that modifying PEI with CQDs can increase the molecular weight of PEI.

[0100] Application Example 1

[0101] This application example illustrates the method for preparing a gel.

[0102] Polyacrylamide was mixed with distilled water, and then PEI or PEI-CQDs were added. The mixture was reacted at 90°C for 12 hours. The mass ratio of polyacrylamide to PEI or PEI-CQDs composite was 100:8, and the mass ratio of polyacrylamide to water was 5:100. Samples without PEI or PEI-CQDs were designated as blank controls. 600 PEI 1800 PEI 10000 The PEI-CQDs composite materials are the PEI-CQDs composite materials prepared in Example 1 above (PEI... 600 -CQDs, PEI 1800-CQDs, PEI 10000 -CQDs), and recorded the gelation time of different experimental groups. The results are shown in Table 2.

[0103] The gelation reaction process was observed using differential scanning calorimetry (DSC): the dynamic DSC scan showed two consecutive peaks. Due to PAM hydrolysis, an absorption peak was observed at around 60℃, and another exothermic peak was observed at around 70℃, which corresponds to the beginning of crosslinking of PAM with PEI or PEI-CQDs.

[0104] Table 2

[0105]

[0106]

[0107] As can be seen from Table 2 above, in the blank control group or with only low molecular weight PEI (PEI) added 600 When using PEI, a gel cannot be formed, but when using PEI... 600 -CQDs can form gels, and their gelation time is shorter than that of PEI. 1800 The gel time was significantly shortened by using PEI-CQDs composite materials, as observed in other experimental groups.

[0108] Application Example 2

[0109] Polyacrylamide was mixed with distilled water, and then a certain amount of PEI-CQD composite material was added. Its gelation behavior at 70℃ was observed. The gelation time and strength were determined by observing the gelation state using the gel coding method. A gelation time was considered to be when the gel strength reached grade C. The gel strength (GSC) of the plugging agent was divided into 10 grades based on visual inspection using the SYDANSK gel coding method, as shown in Table 3.

[0110] Table 3

[0111]

[0112]

[0113] The experimental group includes:

[0114] (1) Blank control: Dissolve 0.5g PAM in 12mL of deionized water, place it in a vial and seal it, and observe the gelation at 70℃.

[0115] (2) PEI group: Dissolve 0.5g PAM in 10mL of deionized water, and add 2mL of PEI (PEI with different molecular weights) with a mass fraction of 5%. 3000 PEI 10000PEI 25000 The solution was placed in a vial and sealed to obtain PAM / PEI. 3000 PAM / PEI 10000 PAM / PEI 25000 The gel was observed at 70℃.

[0116] (3) PEI-CQDs group: 0.5g PAM was dissolved in 10mL of deionized water, and 2mL of PEI-CQDs (PEI-CQDs) with different molecular weights and a mass fraction of 5% were added to the solution. 3000 -CQDs, PEI 1000 -CQDs, PEI 25000 -CQDs), placed in a vial and sealed, yield PAM / CQDs / PEI. 3000 PAM / CQDs / PEI 10000 PAM / CQDs / PEI 25000 The gel was observed at 70℃.

[0117] The results of gelation time and gelation strength are shown in Table 4. Figure 8 PEI of different molecular weights (from left to right: PAM / PEI) 3000 PAM / PEI 10000 PAM / PEI 25000 Gel image of the prepared PAM / PEI; Figure 9 PEI of different molecular weights (from left to right: PAM / CQDs / PEI) 3000 PAM / CQDs / PEI 10000 PAM / CQDs / PEI 25000 Gel image of the prepared PAM / CQDs / PEI.

[0118] Table 4

[0119]

[0120]

[0121] From Table 4 and Figure 9 As can be seen, the higher the molecular weight of PEI, the shorter the gelation time and the greater the gel strength. Furthermore, it is related to... Figure 8 The comparison shows that the gel strength is greater with the presence of CQDs. This suggests that CQDs may act as crosslinking agents in the crosslinking system, accelerating the formation and strengthening the three-dimensional network structure. This structure can contain water within the crystal lattice, forming a viscoelastic gel. Therefore, grafting PEI with CQDs can effectively increase the molecular weight and branching degree of PEI, thus improving its performance as a gel-based water-blocking agent.

[0122] Figure 10 Gel images prepared with different amounts of CQDs, where the left image shows 0.05g PAM and 2mL PEI. 25000 -CQDs, PEI:CQDs=10:1 (mass ratio), the right figure shows 0.05g PAM, 2mL PEI 25000 -CQDs, where PEI:CQDs = 5:1 (mass ratio). It can be seen that the mass ratio of CQDs to PEI affects the gelation effect; within a certain range, the more CQDs added, the better the gelation effect.

[0123] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. The application of a PEI-CQDs composite material in the preparation of polyacrylamide gel, characterized in that, The preparation method of the PEI-CQDs composite material includes: (1) Electrolyze graphite in water to obtain carbon quantum dots; (2) Carbon quantum dots and polyethyleneimine are reacted in the presence of optional additives to obtain PEI-CQDs composite material; The PEI-CQDs composite material contains carbon quantum dot covalently modified polyethyleneimine; Among them, the molar ratio of hydroxyl to carbonyl groups in the oxygen-containing functional groups on the surface of carbon quantum dots is less than 1; In step (2), the ratio of polyethyleneimine to carbon quantum dots by weight is 0.1-20:1; The weight-average molecular weight of the polyethyleneimine is 500-50000 g / mol.

2. The application according to claim 1, wherein, In step (1), the preparation method of the carbon quantum dots includes: using a graphite rod as the anode and cathode, electrolyzing water with a DC power supply to obtain an electrolyte, purifying the electrolyte, and obtaining carbon quantum dots.

3. The application according to claim 2, wherein, The cathode graphite rod and the anode graphite rod are spaced 3-15 cm apart; And / or, the voltage is 5-50V; And / or, the electrical conductivity of the water is less than 10 μS / cm; And / or, in the oxygen-containing functional groups on the surface of carbon quantum dots, the molar ratio of hydroxyl to carbonyl groups is 0.2-0.

6.

4. The application according to claim 3, wherein, The distance between the cathode graphite rod and the anode graphite rod is 5-10 cm; And / or, the voltage is 10-40V.

5. The application according to claim 1, wherein, In step (2), the ratio of polyethyleneimine to carbon quantum dots by weight is 1-15:1; and / or The weight-average molecular weight of the polyethyleneimine is 600-20000 g / mol.

6. The application according to claim 1, wherein, In step (2), the additive comprises a crosslinking agent and / or an amino protecting agent; and / or The reaction is carried out in an aqueous system.

7. The application according to claim 6, wherein, The crosslinking agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride; And / or, the amino protecting agent is N-hydroxysuccinimide; And / or, by weight, the ratio of carbon quantum dots, crosslinking agent and amino protectant is 1:0.2-10:0.1-5.

8. The application according to claim 7, wherein, The ratio of carbon quantum dots, crosslinking agent and amino protectant by weight is 1:0.5-5:0.2-2.

9. The application according to claim 1, wherein, The infrared spectrum of the PEI-CQDs composite material includes 1632-1638 cm⁻¹. -1 The stretching vibration at point C=C.

10. A method for preparing a gel, characterized in that, The method comprises: contacting and reacting the PEI-CQDs composite material according to any one of claims 1-9 with polyacrylamide in the presence of water to obtain a gel.

11. The method according to claim 10, wherein, The reaction conditions include a temperature of 60-120℃; And / or, by weight, the ratio of polyacrylamide to PEI-CQDs is 100:2-20; And / or, by weight, the mass ratio of polyacrylamide to water is 0.1-15:

100.

12. The method according to claim 11, wherein, The reaction conditions include a temperature of 80-110℃.

13. The gel prepared by the method according to any one of claims 10-12.

Citation Information

Patent Citations

  • Strontium titanate-carbon quantum dot composite material and preparation method and application thereof

    CN111036188A

  • Preparation method and application of fluorescent hydrogel dressing

    CN112358646A

  • Carbon material for detecting iron ions as well as synthesis method and application of carbon material

    CN114956048A